A Simple Effective Protocol to Increase Prenatal Detection of Critical Congenital Heart Disease. (March 2014) - Letourneau, Karen M.; McDonald, Keith; Soni, Reeni; Karlicki, Fern; Horne, David; Hall, Philip F.; Fransoo, Randall
Prenatal diagnosis of congenital heart disease (CHD) during routine obstetric sonography has been aptly named the sonographer's Achilles heel. Although CHD occurs more commonly than any other major congenital abnormality, the detection rate remains low. The goal of this study was to improve the prenatal diagnosis of CHD during routine obstetric sonography through the development and implementation of a simple and effective screening protocol.